2021
DOI: 10.1016/j.str.2020.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM Structure of K+-Bound hERG Channel Complexed with the Blocker Astemizole

Abstract: Highlights d Cryo-EM structure of hERG channel complexed with astemizole was revealed d Potassium ions were found in the selectivity filter of hERG channel structures d Astemizole inhibits K + flux by occluding the intracellular pore of selectivity filter d Astemizole has several types of interactions with the binding site

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 47 publications
3
57
0
Order By: Relevance
“…Many potassium channels are blocked by compounds that act within the central cavity 124 126 , 146 and functional studies have long indicated that K 2P s share this proclivity for block from the intracellular side 74 , 142 , 147 ( Table 1 ). Structural definition of the Vestibule site delimited by the X-gate in K 2P 3.1 (TASK-1) 38 together with prior studies identifying the TASK subfamily central cavity as a hotspot for the action of a varied antagonists 111 highlight the potential for modulators to act in the K 2P inner cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Many potassium channels are blocked by compounds that act within the central cavity 124 126 , 146 and functional studies have long indicated that K 2P s share this proclivity for block from the intracellular side 74 , 142 , 147 ( Table 1 ). Structural definition of the Vestibule site delimited by the X-gate in K 2P 3.1 (TASK-1) 38 together with prior studies identifying the TASK subfamily central cavity as a hotspot for the action of a varied antagonists 111 highlight the potential for modulators to act in the K 2P inner cavity.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggest that the structure may be in a possible inactivated state when compared to a non-inactivating S631A mutant with F627 shifted slightly into the conduction path. However, a more recent cryo-EM structure of a proposed inactivated state of hERG also shows F627 pointed away from the conduction path, but with a nearly 2 Å increase between carbonyl oxygens in the S1 position; inactivation in this case being the loss of K + ion coordination, not necessarily the orientation of F627 (Asai et al, 2021). In comparison, our m1 and m2 cryo-EM-refined starting models have S1 diameters of 7.2 Å; more open than their archetype hERG structure, but clearly more constricted than the newly proposed inactivated structure.…”
Section: Discussionmentioning
confidence: 96%
“…4) The first cryo-EM hERG structures solved by Wang et al [28], in which the authors proposed that blockers occupy some or all of the "hydrophobic pockets" residing inferior to the selectivity filter. 5) A recent cryo-EM structure of astemizole-bound hERG solved by Asai et al [7] (7CN1). 6) Recent cryo-EM structures of flecainide and quinidine-bound Nav1.5, in which both blockers are fully buried within the pore (as claimed for astemizole-bound hERG and may be assumed for other hERG blockers as well).…”
Section: Discussion Herg Blockers Undergo Atypical Bindingmentioning
confidence: 99%
“…Astemizole was docked in the astemizole-bound structure (PDB code = 7CN1 [7]) using the Glide tool in Maestro (noting that astemizole was omitted from this structure for unexplained reasons).…”
Section: ) Bright Blue = 100% H Visitsmentioning
confidence: 99%